2013
DOI: 10.1371/journal.pone.0079840
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Related Mortality among Adults in Rural Western Kenya: Characterising Deaths Using Data from a Health and Demographic Surveillance System

Abstract: BackgroundInformation on trauma-related deaths in low and middle income countries is limited but needed to target public health interventions. Data from a health and demographic surveillance system (HDSS) were examined to characterise such deaths in rural western Kenya.Methods And FindingsVerbal autopsy data were analysed. Of 11,147 adult deaths between 2003 and 2008, 447 (4%) were attributed to trauma; 71% of these were in males. Trauma contributed 17% of all deaths in males 15 to 24 years; on a population ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Similarly, despite broad decreases in age-standardised rates of injury burden, the pace of progress for these causes has been comparatively slow and ultimately has led to minimal changes in the proportion of overall burden due to injuries during the past 25 years. Prevention of injuries requires strong public safety policies, 53 but minimising mortality and long-term disability from injuries hinges upon having comprehensive trauma care systems54, 55 that provide timely, evidence-based care,56, 57, 58 including emergency surgical services 59, 60…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, despite broad decreases in age-standardised rates of injury burden, the pace of progress for these causes has been comparatively slow and ultimately has led to minimal changes in the proportion of overall burden due to injuries during the past 25 years. Prevention of injuries requires strong public safety policies, 53 but minimising mortality and long-term disability from injuries hinges upon having comprehensive trauma care systems54, 55 that provide timely, evidence-based care,56, 57, 58 including emergency surgical services 59, 60…”
Section: Discussionmentioning
confidence: 99%
“…al. who found that 4% of deaths were attributable to injuries [13]. While the global burden of injuries is on the decline [1], the burden of injuries in especially Sub-Saharan Africa remains high, possibly due to inadequate preventive measures, increased motorization and industrialization and weak health response [5].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in an informal settlement in Nairobi also found assault to be the leading cause of injury fatality [27]. Additionaly, another study in Western Kenya found that assault was the leading cause of injury fatality in men [13]. The homicide rate in Africa is the second highest in the world at 10.9 per 100,000 after the America’s region [28].…”
Section: Discussionmentioning
confidence: 99%
“…Between 2003 and 2008, the proportion of deaths related to trauma in western Kenya increased from 2.5% to 5·9%, with road traffic accidents (RTA) the the leading cause 5. In the past, most Kenya public health programmes focused on communicable diseases.…”
Section: Introductionmentioning
confidence: 99%